Ningaloo Coast region statistics: collected for the Ningaloo destination modelling project - Jones, Tod; Hughes, Michael; Wood, David; Lewis, Anna; Chandler, P. (Sustainable Tourism CRC, 2010)
This report provides the latest information about the characteristics and behaviours of visitors for the tourism industry, managers, and other research projects based in the Ningaloo Coastal Region.The Ningaloo Destination Modelling (NDM) project is a collaborative project between researchers from seven Australian universities and Sustainable Tourism Cooperative Research Centre that will deliver a scenario planning tool that assesses the social, environmental and economic impact of tourism planning strategies in order to assist tourism planning in a regionthat relies on its unique natural attractions